Tenomodulin promotes human adipocyte differentiation and beneficial visceral adipose tissue expansion - Senol-Cosar, Ozlem (Nat Commun, 2016)
Proper regulation of energy storage in adipose tissue is crucial for maintaining insulin sensitivity and molecules contributing to this process have not been fully revealed. Here we show that type II transmembrane protein tenomodulin (TNMD) is upregulated in adipose tissue of insulin-resistant versus insulin-sensitive individuals, who were matched for body mass index (BMI). TNMD expression increases in human preadipocytes during differentiation, whereas silencing TNMD blocks adipogenesis. Upon high-fat diet feeding, transgenic mice overexpressing Tnmd develop increased epididymal white adipose tissue (eWAT) mass, and preadipocytes derived from Tnmd transgenic mice display greater proliferation, consistent with elevated adipogenesis. In Tnmd transgenic mice, lipogenic genes are upregulated in eWAT, as is Ucp1 in brown fat, while liver triglyceride accumulation is attenuated. Despite expanded eWAT, transgenic animals display improved systemic insulin sensitivity, decreased collagen deposition and inflammation in eWAT, and increased insulin stimulation of Akt phosphorylation. Our data suggest that TNMD acts as a protective factor in visceral adipose tissue to alleviate insulin resistance in obesity.